2017
DOI: 10.1016/j.ijid.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B virus and hepatitis C virus co-infection among people living with HIV/AIDS visiting antiretroviral therapy centres in Nepal: a first nationally representative study

Abstract: Objectives: To assess the prevalence of human immunodeficiency virus (HIV), hepatitis C virus (HCV), and hepatitis B virus (HBV) co-infections among people living with HIV (PLHIV) in Nepal. Methods: A sample of 677 PLHIV representing key affected populations (KAP) in Nepal, who were undergoing antiretroviral (ART) therapy in ART clinics around the country, were voluntarily enrolled in the study. Rapid kit-based testing followed by ELISA for validation was performed, focusing on HBV surface antigen (HBsAg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
(16 reference statements)
8
14
0
1
Order By: Relevance
“…A study carried out in Nepal during 2010-2011 reported that the prevalence of HBV and HCV confections among the HIV-positive population was 4.4% and 19%, respectively [ 23 ]. Those reported rates are both significantly higher than those of our current study.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Nepal during 2010-2011 reported that the prevalence of HBV and HCV confections among the HIV-positive population was 4.4% and 19%, respectively [ 23 ]. Those reported rates are both significantly higher than those of our current study.…”
Section: Discussionmentioning
confidence: 99%
“… 4 10–15 Such data are especially scarce in developing countries with high burden of each of these infections, such as Rwanda. 12 16 In 2015, Rwanda DHS showed that the prevalence of HIV in the general population was 3%, with a higher prevalence in urban than rural areas (6% vs 2.4%, respectively). 17 Recent studies on HBV in Rwanda revealed that the prevalence of hepatitis B surface antigen (HBsAg) among people screened was 3.9%, 18 19 while the prevalence of anti-HCV was between 6.2% and 6.6% with viremia of 52%.…”
Section: Introductionmentioning
confidence: 99%
“…Also, 7.1% of HBV, 18.1% of HCV, and 0.5% of HBV/HCV infection living with HIV were observed in people who inject drugs [12]. The first nationally representative cross-sectional study on people living with HIV and female sex workers revealed 4.4% of HBV, 19% of HCV, and 1% of HBV/HCV coinfection [15]. However, the prevalence of HCV could be higher than that of HBV coinfection in HIV-infected patients due to the availability of HBV vaccines.…”
Section: Discussionmentioning
confidence: 99%